Hospital public relations and internal communication barriers during the Covid-19 pandemic - Lestari, Eni; Rahmanto, Andre Noevi; Satyawan, Ignatius Agung (Universitas Padjadjaran, 2023)
Background: Covid-19 hit almost all sectors of life, including the economy, tourism, and hospitals. Long queues of patients in the waiting rooms, mandatory use of personal protective equipment, layered masks, maintaining distance in interaction, and use of medical terms in requesting messages to patients are the barriers for medical personnel, especially nurses, in communication with patients. Purpose: The current study examined how hospital public relation helps overcome communication barriers between nurses and patients. The study was conducted at PKU Muhamadiyah Hospital Surakarta, accredited with 6-star KARS as a provincial referral hospital for COVID-19 patients and has the highest patient occupancy in Surakarta. Methods: It is a descriptive qualitative study. Conclusion: By using Dozier and Broom’s theory regarding the role of PR, this study proved that PR successfully helps overcome internal communication barriers experienced by nurses and patients. It plays as an expert advisor by providing input to hospital management and bridging the communication between nurses and patients. PR also acts as a problem solver by providing training on communicating correctly. Implications: Communication barriers can be overcome if nurses have good communication skills and understanding. As a support for the hospital system, PR provides regular communication training for nurses struggling to serve patients during the covid-19 pandemic.